2019
DOI: 10.1016/j.ejpn.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy among children of immigrants in Denmark and the role of socioeconomic status

Abstract: Background: Children of immigrants in Denmark have excess risk for some of the most wellestablished risk factors for cerebral palsy (CP). Objectives: To study differences in risk of CP between children of immigrants and children of Danish-born mothers, and explore whether socioeconomic status drives any potential association. Methods: A register-based cohort study including 1,274,616 children born in Denmark between 1981 and 2007. Of these, 2807 had a validated CP diagnosis in the Danish CP Register. We estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In a study conducted in Denmark, it is reported that there is no statistically significant difference between maternal smoking during pregnancy and CP risk factors. [ 25 ] The rate of smoking during pregnancy of the mothers included in the study was 18% and the rate of exposure to cigarette smoke during pregnancy was 41%. In a study conducted in Japan, maternal alcohol use during pregnancy was found to be a risk factor for CP, and severe alcohol consumption was shown to be a cause of many neurodevelopmental abnormalities, including CP.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Denmark, it is reported that there is no statistically significant difference between maternal smoking during pregnancy and CP risk factors. [ 25 ] The rate of smoking during pregnancy of the mothers included in the study was 18% and the rate of exposure to cigarette smoke during pregnancy was 41%. In a study conducted in Japan, maternal alcohol use during pregnancy was found to be a risk factor for CP, and severe alcohol consumption was shown to be a cause of many neurodevelopmental abnormalities, including CP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent population-based studies from around the world reported that the prevalence of CP was ranging from 1 to nearly 4 per 1,000 live births [ 4 ]. The prevalence of CP is variably reported across different countries which are 1.89 per 1,000 live births in Norway [ 10 ], and 2.2 per 1,000 live births in Denmark [ 11 ]. Furthermore, a population-based study in Bangladesh reported that 3.4 per 1,000 children [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a population-based study in Uganda revealed that the prevalence of CP was 2.9 per 1,000 children in 2017 [ 19 ]. In line with the global trend, CP places a heavy burden of disease on children, families, and society in both developed and developing countries [ 4 , 11 ]. The previous studies done in different countries showed that several factors were associated with CP.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to native‐born mothers, immigrants from outside Europe have been reported to present with higher rates of intra‐uterine growth restriction, preterm delivery and congenital malformations. Cerebral palsy is also known to be more prevalent among ethnic minorities 3 . Although these issues are often exacerbated by less than optimal socioeconomic conditions, they are also affected by less than adequate policies, which result in a lack of appropriate family and social support and limitations in accessing local information in the new country.…”
mentioning
confidence: 99%